OPPORTUNITIES FOR AGRICULTURAL ENTREPRENEURSHIP THROUGH THE SHARING ECONOMY: A FOCUS ON FOOD REUSE - Besiana Hoxha (Journal of Bio-Based Marketing)
Agricultural entrepreneurship encompasses activities related to the production, processing, and distribution of agricultural products, demanding innovation and adaptability to changing market and environmental conditions. This sector faces challenges such as climate change and market fluctuations but also leverages advanced technologies to improve operations. Integrating agricultural entrepreneurship with the sharing economy presents new opportunities for sustainability by promoting resource reuse and waste reduction. While the sharing economy lacks a singular definition, it broadly refers to the reutilization of underutilized assets and resources. Sharing economy models include on-demand resource access, automated marketplaces, and on-demand services. In rural areas, this approach may involve the shared use of homes, land, and tools, yielding economic, social, and environmental benefits. In waste management, trust and gratitude have been cultivated as social constructs. Research indicates that the sharing economy enhances productivity, reduces costs, and optimizes resource use, offering numerous advantages compared to its drawbacks, particularly in tourism and waste management. This study aims to explore developmental opportunities for agricultural entrepreneurship through the application of sharing economy principles, with a specific focus on food reuse.